Regarding the Role of the Spatial Development Strategy in he Territorial Planning System of the Russian Federation - Galina A. Lebedinskaya (Academia: Архитектура и строительство, 2018)
planning; proofs are the existence of a plan three-dimensionality of space, methods of its description and structuring (transport natural frameworks, etc.). The spatial development strategy is essential^ an integral conceptual part of the territorial planning, the consistency and direction of the development of space, the choice of priority directions for the development of territorial and economic systems the establishment of the ratio of urbanized and natural territories that ensure their sustainable development At the same time, the spatial development strategy as a part of the territorial planning system of the Russian Federation is not formalized and is considered as a missinglink in the system of its documents; the missinglevels for which in the Town Planning Code of the Russian Federation it is necessary to give the concept of a spatial development strategy are thelevels of the country as a whole, the macroregion and urban agglomerations. The spatial development strategy is proposed to be defined as the main and general plan for the development of the territorial object (the system of resettlement the subject of the Russian Federation in a municipal district city, agglomeration), designed as a strategic planning document that defines the priorities, goals direction, scope andlimitationsof spatial development in thelong term. For urban agglomerations this is the minimum necessaiy document that precedes territorial planning at the level of cities urban districts and municipal districts the basis for the development of a program of measures for the socio-economic development strategy and its implementation program, for joint planning of urban and rural settlements; the obligatory nature of their planning is to be determined in the Town Planning Code of the Russian Federation and in the Law *0n Strategic Planning".